Epidemiology of Hypertension in a Typical State-Level Poverty-Stricken County in China and Evaluation of a Whole Population Health Prevention Project Intervention - Zhengye Li; Xingyu Liu; Zhongan Zhang; Li Huang; Qing Zhong; Renlin He; Pei Chen; Ailin Li; Jun Liang; Jianbo Lei (International Journal of Hypertension)
Background. In China, there were 584 state-level, poverty-stricken counties until January 2019. The central government has invested a large amount of funds and preferential policies to alleviate poverty in these areas. The Whole Population Preventive Healthcare Pilot Project (WPPHCPP) aims to explore the use of limited funds to achieve healthy poverty alleviation through free regular physical examinations and comprehensive health management for the entire population in impoverished regions. Objective. By demonstrating the prevalence of hypertension in populations of poverty-stricken counties in Western China and evaluating health management outcomes after implementing the WPPHCPP, we can provide a foundation for the future development and promotion of improved public health. Subjects and Methods. Through the WPPHCPP, the entire population in the pilot area was required to undergo free physical examinations. The examinations screened for hypertension revealed the epidemiology of adult hypertension. Based on blood pressure levels and risk factor exposures, risk classifications for hypertensive patients were performed. Corresponding intervention and management strategies for different risk levels were provided by a joint management team consisting of family physicians from three different levels of local medical institutions (village, town, and county). Healthcare management outcomes including awareness, treatment, and hypertension disease rates were compared between the period before and after the intervention and management. Results. By the end of 2017, among the 452,200 permanent residents in the region, 285,458 adults had completed the physical examination. The prevalence of hypertension was 18.5%, which was lower than the national average of rural areas (28.8%). The prevalence of hypertension in men (18.7%) was slightly higher than that of women (18.3%). The prevalence of hypertension increases with age; for people aged >65 years, it was 39.2%. There were 15,074 newly discovered hypertensive patients in the WPPHCPP, accounting for 29.6% of the total hypertensive population in the region. Regarding the management outcomes, the rates of management and standardized management of hypertension increased each year between 2015 and 2017. Although the rate of disease control management decreased slightly, the overall level of management remained significant. The awareness and treatment rates of hypertension also increased over the years and peaked at 95.0% and 94.9%, respectively, in 2017. The disease control rate was 45.6% in 2016, which was the highest among the years assessed. All the above parameters were better than the national average of rural areas. From 2015 to 2017, the number of people with high-risk factors for hypertension and percentage of high-risk patients decreased from 33,064 to 26,982 and 27.4% to 24.6%, respectively. The percentage of the population exposed to cigarettes and alcohol decreased from 30.6% to 27.2% and 25.1% to 22.0%, respectively. The number of deaths due to hypertensive cardiovascular or cerebrovascular diseases decreased each year and was 275 (39.55/100,000 people) in 2017, which was the lowest rate measured. The annual growth of cardiovascular or cerebrovascular diseases remained negative. Conclusions. The overall prevalence of hypertension in the studied area was lower than the national average of rural areas. The health management model of “government-led joint efforts of three levels of medical institutions (village, town, and county) with active participation of local village communities” improved the management outcomes of hypertensive patients and fulfilled the latest advocacy of the prevention and control of chronic diseases by the United Nations. This model can be considered an effective model for healthcare management practice in similar situations.